Antidiabetic Potential of Phytochemicals Found in Vernonia amygdalina - Archna Talwar; Neha Chakraborty; Manaal Zahera; Shruti Anand; Irshad Ahmad; Samra Siddiqui; Avni Nayyar; Ashanul Haque; Mohd Saeed (Journal of Chemistry)
Type 2 diabetes mellitus (T2DM), or “insulin-independent diabetes mellitus,” is a worldwide health concern. Diabetes affects roughly 415 million individuals worldwide, with 193 million undiagnosed cases. The number of people afflicted in the following decades is predicted to double. Although various synthetic medications are currently available to treat/manage T2DM, their side effects compel researchers to seek novel treatment options. Because of their affinity for biological receptors and broad bioactivity, nature has long been a source of innovative medication. V. amygdalina is one of the numerous natural productswith antidiabetic properties. Several studies have shown that the extracts have antidiabetic effects in vitro and in vivo. This review examined the antidiabetic and pharmacokinetic characteristics of phytoconstituents found in V. amygdalina.